Implementasi Algoritma Support Vector Machine Untuk Klasifikasi Status Stunting Pada Balita - Abdul Jalil; Ahmad Homaidi; Zaehol Fatah (Universitas Islam Raden Rahmat, Malang, 2024)
In Indonesia, the main health problem is stunting or dwarfism in toddlers due to chronic malnutrition. This study uses the Support Vector Machine (SVM) algorithm to classify the stunting status of toddlers with high accuracy. The dataset for stunting cases in Indonesia, which includes 6500 data, consists of eight attributes: